Mediasi Sebagai Alternatif Penyelesaian Tindak Pidana Penganiayaan Ringan yang Dilakukan oleh Anak di Kabupaten Gianyar - Dewa Gede Agung Getsumeda; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2021)
For parties who wish to resolve disputes without trial or arbitration, alternative dispute resolution is an option. This choice is entirely dependent on the wishes of the disputing parties. There is a dispute between the two parties so that each party can choose the method used. This study aims to determine the legal regulation of minor maltreatment committed by children through mediation and to find out the legal consequences if minor maltreatment crimes committed by children are resolved through mediation. The type of research used is normative legal research. Primary data is obtained from field reviews while secondary data is obtained from articles, laws and regulations, from books. In addition to these provisions, minor violations that can be resolved through mediation are criminal acts which can be in the form of confinement or imprisonment for a maximum of 3 (three) months or a maximum of Rp. 7,500.00 (Seven thousand five hundred). Criminal offenses committed by children under 8 years. The conclusion of this study is that the legal consequences if the crime of minor maltreatment committed by children is resolved through mediation, including settlement through deliberation, peace and agreement of the perpetrator, victim and family so as to produce a win-win solution. A peaceful settlement is basically an agreement that the parties consider good from all other ways.